Pengembangan Buah dan Sayur Organik Sebagai Oleh-Oleh Wisata Daerah Pegunungan - Aliyah, Istijabul -; Pujiasmanto, Bambang - (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
Mountainous areas have a lot of tourism potential, including organic agriculture-based agro-tourism. However, there are still some problems faced by the farming community such as limited skills regarding processing of agricultural products in the form of organic fruits and vegetables as souvenirs typical of mountain tourism. limitation of packaging creativity that meets the health and safety feasibility standards of organic fruits and vegetables as tourist souvenirs that are easily carried by tourists, and marketing of agricultural products in the form of organic fruits and vegetables to attract tourists and the wider community. The methods to be used include methods counseling and training as a means of transfer of knowledge about the processing, packaging and marketing of organic agriculture and the ins and outs of which will be provided to partners, assistance methods to enhance partners' creativity and performance in processing, packaging and marketing agricultural products in the form of organic fruit and vegetables as souvenirs for tourism typical of mountainous areas in the economic development of society and regional tourism, and the provision of packaging equipment to implement packaging that meets hygiene, health and food safety standards, and the creation of a website as a medium for expanding the network to improve a tourist attraction. The targeted results are an increase in skills in processing, packaging, and marketing agricultural products in the form of organic fruit and vegetables as souvenirs typical of mountain tourism, diversification of processed organic plant products as souvenirs typical of an area, the addition of facilities in the form of packaging tools (wrapping mechine) for packaging organic fruits and vegetables so that they are easy to carry as souvenirs for a typical tourist area, the expansion of marketing networks